A framework for green supply chain management in construction sector: A case study in Indonesia - I. Putu Artama Wiguna; Farida Rachmawati; M. Arif Rohman; Larashati B'tari Setyaning (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: In order to implement Green Supply Chain Management (GSCM to support the effort in reducing the environmental impact of the supply chain processes, a framework needs to be developed. This study aimed to propose a conceptual and holistic GSCM framework to represents a roadmap towards GSCM implementation by integrating all green supply chain practices by various stakeholders of construction sector in Indonesia. Design/methodology/approach: Green practices were obtained from an extensive literature review. Questionnaire survey of GSCM stakeholders in the construction sector was conducted to obtain the preference of green supply chain variables as the proxy for variable weighting and ranking. Pairwise Comparison (PWC) and Technique for Others Preference by Similarity to Ideal (TOPSIS) were adopted to analyze the weight and to rank the green practices respectively. The finding of PWC and TOPSIS were used to develop the framework. Findings: The implementation of the GSCM in the construction sector in Indonesia is mainly focused on reducing the use of hazardous materials, the management of waste at the project site, selling products and components that are no longer used, using video conferencing both inter- and intra-organization meetings, and support from the management level in the form EMS and ISO 14001 certification. Research limitations/implications: This study did not include other GSCM performances as criteria, such as operational and logistical performance. Practical implications: An efficient evaluation technique developed by the framework can be used in decision making policies by policy makers and stakeholders of the organization which can identify and prioritize the green practices for adoption of GSCM in the construction sector. Originality/value: The originality of this research is that GSCM framework was developed with most relevant green practices based on ranking and weighting criteria as well as the main stakeholders involved.
Keywords: 650; construction sector; framework; GSCM; PWC; TOPSIS